Peran Pendidikan Agama Islam dalam Membentuk Karakter Religius Siswa Sekolah Dasar - Yunike Widianti; Parrisca Indra Perdana (Jurnal Ilmiah Dan Karya Mahasiswa, 2024)
The purpose of this study is to investigate the role of Islamic Religious Education (PAI) in influencing the religious character of pupils at Demangan 1 State Elementary School. Islamic Religious Education teachers in class III and students in class III B serve as the research subjects for this study, which employs a descriptive qualitative methodology. A descriptive qualitative method was used to collect the data. Interviews, observations, and documentation were used to gather data. The results showed that the habits taught in PAI learning include praying, reading short surahs, chanting asmaul husna, cultum before learning, and habituation of adab, kindness, and alms. The character of students is generally quite good, although in the aspect of moral creed still needs further guidance. Islamic Religious Education plays an important role in shaping students' religious character through instilling the values of creed, Al-Quran, hadith, fiqh, and Islamic history, which guide daily behavior. The creed becomes the moral foundation of students, helping them understand fundamental religious values.